Greenhouse Monitoring and Controlling Using Arduino - Arathi. P; Krishnan, Archana; D YaminiKrishna; Y R, Gagana; Patel, Gayanand (International Journal of Engineering and Management Research, 2023)
A greenhouse is structure that's erected of walls and a transparent roof. But to get the asked results there are some veritably important factors which come into a play like Temperature, Moisture, Light, and Water, which are necessary for better plant growth. It's designed to maintain regulated climatic conditions. These structures are used for the civilization of shops, fruits, and vegetables which bear a particular position of sun, temperature, moisture, and soil humidity. IOT and Arduino grounded Greenhouse Environment Monitoring and Controlling is designed to maintain these conditions in the greenhouse. Observation agrarian surroundings for varied factors similar as temperature and humidness on with indispensable factors are frequently of significance. The power to document and detail changes in parameters of interest has come more and more precious. This system helps in monitoring and controlling the climatic conditions that are favorable for the cultivation of plants. By using this system, crop growth can be bettered along with maximized yield, irrespective of the rainfall conditions.